Investigation of Crack Propagation and Healing of Asphalt Concrete Using Digital Image Correlation - Navid Hasheminejad; Cedric Vuye; Alexandros Margaritis; Bart Ribbens; Geert Jacobs; Johan Blom; Wim Van den bergh; Joris Dirckx; Steve Vanlanduit (Applied Sciences, 2019)
The fatigue performance and healing ability of asphalt pavements are important for mixture design, rehabilitation, and maintenance of the roads. By analyzing these parameters in an asphalt mixture, it is possible to predict the crack formation and propagation in asphalt pavements and healing of these cracks during the rest periods. The healing effect in asphalt mixtures has been observed and verified by many researchers and different methods exist to evaluate this phenomenon. However, current methods are still inadequate to fully observe and quantify the healing phenomenon in asphalt mixtures. In this study, a digital image correlation (DIC) method is used to calculate the strain map on the surface of cylindrical asphalt specimens during the indirect tensile fatigue test. This strain map is used to detect the location of crack initiations and development of the microcracks during the experiments. Next, the specimens are unloaded and the temperature of the climate chamber is increased to 60 °C for 18 h to investigate the healing phenomenon on the surface of the specimens. It is observed that the strain reduces near the microcrack areas especially at the tip of the microcracks. Furthermore, using DIC it is possible to observe the healing rate and the minimum time required to heal the microcracks on the surface of the specimens.